GeoGebra-based flipped learning model: An alternative panacea to improve student’s learning independency in online mathematics learning - Naufal Ishartono; Adi Nurcahyo; Mohamad Waluyo; Rafiza Abdul Razak; Suliadi Firdaus Sufahani; Millenia Hanifah (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2022)
Previous studies have tried to improve students' independence in online mathematics learning. However, the Flipped Learning model integrated with GeoGebra is scarce as none of the existing syntaxes accommodate the model. As the existing syntax is based on three phases: pre-class activity, in-class activity, and post-class activity. This research aims to develop GeoGebra-based Flipped Learning syntax to increase students' independence in learning mathematics. The main difference between the existing syntax and the developed one is the integration of GeoGebra in the pre-class activity. The integration is based on previous studies showing that using GeoGebra can improve student’s learning achievements. It research employed the Design-Based Research (DBR) model involving 125 second-year undergraduate students of a private university in Indonesia. The syntax results were obtained from the study, indicating an increase in the average value of student independence in learning mathematics based on learning independence, confidence, level of discipline, sense of responsibility, level of initiative, and self-control. This developed syntax is expected to help teachers streamline online mathematics learning.